2023
DOI: 10.3390/nu15020365
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nutritional Factors to Evaluate Periodontal Clinical Parameters in Patients with Systemic Diseases

Abstract: Nutritional factors reflect the periodontal parameters accompanying periodontal status. In this study, the associations between nutritional factors, blood biochemical items, and clinical parameters were examined in patients with systemic diseases. The study participants were 94 patients with heart disease, dyslipidemia, kidney disease, or diabetes mellitus. Weak negative correlation coefficients were found between nine clinical parameters and ten nutritional factors. Stage, grade, mean probing depth (PD), rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Authors concluded that at present, it is unclear whether dietary counselling may improve periodontal treatment outcomes and additional research is needed. More recent study have also suggested that nutritional factors were correlated with staging and grading of periodontitis [ 16 ]. Specifically, consumption of yogurt, tofu, dark green vegetables, cabbage, napa cabbage showed negative weak correlations with stage, grade, PD, rate of PD 4–5 mm, BOP rate, PISA (periodontal inflamed surface area) and PISA/PESA (PESA, periodontal epithelial surface area).…”
Section: Introductionmentioning
confidence: 99%
“…Authors concluded that at present, it is unclear whether dietary counselling may improve periodontal treatment outcomes and additional research is needed. More recent study have also suggested that nutritional factors were correlated with staging and grading of periodontitis [ 16 ]. Specifically, consumption of yogurt, tofu, dark green vegetables, cabbage, napa cabbage showed negative weak correlations with stage, grade, PD, rate of PD 4–5 mm, BOP rate, PISA (periodontal inflamed surface area) and PISA/PESA (PESA, periodontal epithelial surface area).…”
Section: Introductionmentioning
confidence: 99%